Upaya Peningkatan Minat Belajar Bahasa Inggris Siswa-Siswi SDN 06 Salatiga dengan Penggunaan ‘Hands-On’ dan ‘Hands-Off’ Visual Aids - Kisnanto, Yustina Priska; Hadiyanto, Anita Kurniawati (Universitas Nusantara PGRI Kediri, 2024)
English learning at the elementary school level in Indonesia is generally constrained by the limited number of qualified English teachers and the formal learning context in the classroom (not natural). This causes the implementation of this subject to tend to rely on printed books with monotonous delivery. To overcome these obstacles, SDN 06 Salatiga in collaboration with UKSW PBI held a program to teach English using visual aids at the school. This program is divided into preparation, implementation, and evaluation stages, which last for 14 weeks. The implementing team consists of four lecturers, who act as mentors, and 16 students, who act as English class teachers/facilitators for grades 1 and 4 of elementary school. The results of this program are that English learning is better facilitated with the use of various hands-on and hands-off visual aids. In addition, the students' responses to this program are very positive because learning becomes more enjoyable and easier to understand, so that their interest in learning English also increases.